1981
DOI: 10.1111/j.1439-0329.1981.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Rückgang der Tanne (Abies alba Mill.) in Polen

Abstract: Decline of silver fir (Abies alba Mill.) in Poland. On the b.isis of his own observations and of data from the literature, the author gives a review of silver fir diseases, pests and damage by other biotic and abiotic factors in Poland and on conjectural causes of the decline of this tree species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It is a complex disease, since several environmental factors apparently interact with each other, such as drought, frost, strong temperature decreases, competition, pollution, soil acidification, mineral deficiencies, inappropriate silvicultural treatments, insects, and pathogens (Schütt, 1977;Sierpinski, 1981;Larsen, 1986;Krehan, 1989;Bert, 1993;Certini et al, 2000;Thomas et al, 2002). Larsen (1986) indicated that insufficientgenetic variability and low adaptive capacity of the central and western European silver fir may be a predisposing mortality factor, sensu Manion (1981).…”
Section: Introductionmentioning
confidence: 98%
“…It is a complex disease, since several environmental factors apparently interact with each other, such as drought, frost, strong temperature decreases, competition, pollution, soil acidification, mineral deficiencies, inappropriate silvicultural treatments, insects, and pathogens (Schütt, 1977;Sierpinski, 1981;Larsen, 1986;Krehan, 1989;Bert, 1993;Certini et al, 2000;Thomas et al, 2002). Larsen (1986) indicated that insufficientgenetic variability and low adaptive capacity of the central and western European silver fir may be a predisposing mortality factor, sensu Manion (1981).…”
Section: Introductionmentioning
confidence: 98%